Keterampilan Menulis Teks Eksposisi Siswa Menggunakan Metode Think Pair and Share - Neneng Wahyuni (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2020)
The purpose of this study was to determine the effect of the think pair and share method on the exposition of the writing skills of class X SMKN 3 Payakumbuh students. This research method is a quantitative study using the experimental method. The results showed that the mean score of students in the experimental class was 78.37, while in the control class it was 70.62. In conclusion, the think pair and share method affects the writing skills of the exposition text in the experimental class. There is a significant difference in the results of text writing skills using the think pair and share method and conventional methods. Keywords: Expositional Text Writing Skills, Think Pair and Share